Fuling production areas in China: climate and distribution changes (A.D. 618–2100) - Jiang, Yunlu; Ren, Aoyu; Sun, Xue; Yang, Bin; Peng, Huasheng; Huang, Luqi (Frontiers in Plant Science, 2024)
Through a meticulous analysis of ancient Chinese literature, this study comprehensively documents the geographical distribution of Fuling, a traditional Chinese medicinal material, during the Tang, Song, Ming, and Qing dynasties spanning from the seventh to the twentieth century in China. Based on the contemporary distribution information of Fuling, we utilized the maximum entropy (MaxEnt) model to simulate the suitable distribution areas of Fuling in both present-day conditions and under different emission paths in the future (2081~2100). The findings reveal that climate change has influenced the distribution of Fuling production areas. The shifts in Fuling's origin during different periods in ancient and modern times align with climate fluctuations and concurrent societal norms. During the Tang and Song dynasties, Fuling primarily originated in northern China. However, it migrated southward during the Little Ice Age (LIA) and has recently shown a slight northward shift, in line with the climate fluctuations of the LIA and contemporary global warming trends. This study offers a comprehensive analysis of the changes in the distribution and production areas of Fuling over a 1500-year period, encompassing ancient, modern, and future periods. The results provide critical insights for adjusting Fuling cultivation areas in response to climate change and for further exploration of the mechanisms through which climate impacts the growth of Fuling.